Pendapat Siswa tentang Upaya Guru Bimbingandan Konseling dalam Mengembangkan Moral Siswa - Marfita, Yusriza; Zikra, Zikra; Yusri, Yusri (Universitas Negeri Padang, 2013)
Â Abstract:Guidance and counseling teachers play an important rolein developing students' moral, such asmoral knowledge, moral feeling, andmoral behavior. Ideally BK teachers can berole models for students behave. In fact teachers BK can not be agood example for students. The purpose ofthis study was to determinethe extent to which teachers develop students' moral BK. Type of researchis a descriptive study. The study population class XI studentin SMK